2007
DOI: 10.1159/000109228
|View full text |Cite
|
Sign up to set email alerts
|

Maturity of the Myenteric Plexus Is Decreased in the Gastroschisis Rat Model

Abstract: Background: Amniotic fluid (AF) and its components, such as fetal urine and meconium, may lead to intestinal alterations in gastroschisis, which cause immaturity of the myenteric plexus and consequent intestinal hypomotility and malabsorption. In this study we identified morphological and histological alterations of the intestine and the myenteric plexus with two different times of exposure to AF. Methods: The experimental gastroschisis was achieved at two different gestational ages, on day 18.5 (E18.5) and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
4
11
0
2
Order By: Relevance
“…The immaturity picture of the cells responsible for intestinal motor activities presently observed at birth in the baby with GS is very similar to that reported for animal models of GS [8, 11–13, 18]. Moreover, the absence of degenerative processes in all the specimens, together with the presence of a progressive maturative course, supports the hypothesis of a delayed differentiation, rather than an arrest.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The immaturity picture of the cells responsible for intestinal motor activities presently observed at birth in the baby with GS is very similar to that reported for animal models of GS [8, 11–13, 18]. Moreover, the absence of degenerative processes in all the specimens, together with the presence of a progressive maturative course, supports the hypothesis of a delayed differentiation, rather than an arrest.…”
Section: Discussionsupporting
confidence: 83%
“…During the last 10 years a series of articles regarding the possible role of the ICC in the gastrointestinal malformations, including GS, has been published [8, 15–18]. In the rat model of GS, a morphological immaturity of various cell types, including ICC, smooth muscle cells and enteric neurons, has been reported [8, 11–13] thus suggesting a possible explanation for the paralytic ileus characteristic of this malformation. In the present study, the immature features reported for the experimental GS were confirmed by examining samples of small intestine of a baby born with GS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bowel motility is impaired in these patients [Rubin et al, 1978; Simmons and Georgeson, 1996]. Gastroschisis is thought to affect development of intestinal pacemaker cells [Midrio et al, 2004] as well as enteric neurons [Vannucchi et al, 2003; Franca et al, 2007] and can result in either hyper‐ or hypo‐motility. Hypermotility can be controlled with medications, but fewer options are available for the infant with hypomotility.…”
Section: Postnatal and Surgical Managementmentioning
confidence: 99%